A severely cholestatic liver graft can be successfully used in deceased donor liver transplantation. Issue 3 (5th September 2017) - Sakamoto, Seisuke; Sasaki, Kengo; Uchida, Hajime; Narumoto, Soichi; Kitajima, Toshihiro; Irie, Rie; Fukuda, Akinari; Yoshioka, Takako; Kasahara, Mureo
Abstract : The shortage of deceased organs is still a serious issue in Japan. A proactive approach to using liver grafts from extended criteria donors (ECDs) may be one way of expanding the donor pool; however, if it is recklessly attempted, a recipient receiving such a marginal graft can be at risk of mortality due to primary non‐function or delayed graft function. We herein report the successful outcome of a recipient receiving a severely cholestatic graft that was considered transplantable because it lacked features characteristic of a long duration of "cholestasis" according to the precise interpretation of a donor biopsy. Plasma exchange was intentionally introduced to prevent toxic insult by hyperbilirubinemia immediately after transplant. Despite transient acute kidney injury immediately after transplant, the patient's renal impairment was well managed with a renal‐sparing immunosuppressive regimen consisting of basiliximab and mycophenolate mofetil. Although the use of liver grafts from ECDs still needs to be discussed, especially regarding graft selection and allocation policies, efforts not to discard valuable grafts should be undertaken in our country.